Economic Growth, Investment and Employment in the Border Province of Indonesia-Malaysia - Gigin Auliya,; Fariastuti Djafar, (Technium Social Sciences Journal, 2025)
This research examines the effect of employment and investment on economic growth in West Kalimantan, sharing a land border with Sarawak, Malaysia. The study used secondary data covering 14 districts/cities for ten years (2013-2022). The data were analysed by employing the static linear panel data model. The research reveals that investment and employment positively and significantly affect economic growth; the increase in investment and employment will increase economic growth, or vice versa.